2016
DOI: 10.1111/gcbb.12354
|View full text |Cite
|
Sign up to set email alerts
|

Differences in field‐scale N2O flux linked to crop residue removal under two tillage systems in cold climates

Abstract: Residue removal for biofuel production may have unintended consequences for N 2 O emissions from soils, and it is not clear how N 2 O emissions are influenced by crop residue removal from different tillage systems. Thus, we measured field-scale N 2 O flux over 5 years (2005)(2006)(2007)(2010)(2011) from an annual crop rotation to evaluate how N 2 O emissions are influenced by no-till (NT) compared to conventional tillage (CV), and how crop residue removal (RÀ) rather than crop residue return to soil (R+) affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 63 publications
4
23
2
Order By: Relevance
“…This provides evidence that the N 2 O flux was limited by NO 3 and that denitrification in the surface soil was an important source of over-winter N 2 O production (Tenuta and Sparling, 2011). This is consistent with other studies that have indicated de novo N 2 O production was a large N 2 O source over the non-growing season in temperate regions (Wagner-Riddle et al, 2008;Németh et al, 2014;Risk et al, 2014;Congreves et al, 2016). In Winter 2013-2014, there was no apparent correlation between pre-winter NO 3 levels and the mean winter N 2 O fluxes (Fig.…”
Section: Water Extractable Organic Carbon Nitrate and Over-winter Nsupporting
confidence: 90%
See 2 more Smart Citations
“…This provides evidence that the N 2 O flux was limited by NO 3 and that denitrification in the surface soil was an important source of over-winter N 2 O production (Tenuta and Sparling, 2011). This is consistent with other studies that have indicated de novo N 2 O production was a large N 2 O source over the non-growing season in temperate regions (Wagner-Riddle et al, 2008;Németh et al, 2014;Risk et al, 2014;Congreves et al, 2016). In Winter 2013-2014, there was no apparent correlation between pre-winter NO 3 levels and the mean winter N 2 O fluxes (Fig.…”
Section: Water Extractable Organic Carbon Nitrate and Over-winter Nsupporting
confidence: 90%
“…This is consistent with other studies from southern Alberta, Canada, which showed peak N 2 O fluxes during winter (Hao, 2015) or the late-winter to spring period (Chang et al, 1998;Ellert and Janzen, 2008) during the non-growing season. Typically, N 2 O fluxes are greatest during the spring snowmelt in temperate regions (WagnerRiddle and Thurtell, 1998;Johnson et al, 2012;Risk et al, 2013;Congreves et al, 2016). However, our study location typically does not accumulate much snow over-winter.…”
Section: Nitrous Oxide Emissionsmentioning
confidence: 86%
See 1 more Smart Citation
“…Under temperate conditions, Congreves et al . () reported that crop residue reduced N 2 O emissions from four fields and the N 2 O emissions were negatively correlated with dissolved organic carbon. Based on N 2 O reductase gene expression, the authors concluded that plant residues might help in the reduction in N 2 O to N 2 and consequently decrease N 2 O emissions.…”
Section: Discussionmentioning
confidence: 98%
“…Peak frequencies here were modelled via the equation given in Horst (1997). (Furon et al, 2008;Risk et al, 2013;Abalos et al, 2015;Congreves et al, 2017;Wagner-Riddle et al, 2017) with average daily fluxes ranging from 0 to 30 ng N 2 O-N m −2 s −1 (Fig. 3b) Fig.…”
Section: Flux Comparisonsmentioning
confidence: 99%